BEYOND BLACK-LETTER LAW: BRIDGING THEORY AND PRACTICE IN LEGAL EDUCATION - Chaturvedi, Nalin Raj; Vig, Komal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Legal education has historically been a theory driven subject, often detached from the ground realities of legal practice, thus leaving fresh graduates to navigate the labyrinthine of the real world legal challenges on their own. However, with the evolution of time, place and society the legal pedagogy has evolved too. The 21st century has witnessed a significant shift from doctrinal legal education to more hands-on and holistic one, this shift was driven by technological advancements, globalisation and realisation of growing demand of practice-ready graduates. Although legal education has evolved tremendously there still exists a disconnect between doctrines and practice. This paper seeks to trace the evolution of legal pedagogy, critically examine the existing lacunae in the legal education sector, and propose a comprehensive way forward to bridge the gap between theoretical instruction and practical training.